Simulation Of The Trans Binjai Bus Quue Service System Using Poisson And Exponential Distribution Test Results (Case Study: Binjai City Transportation Office) - Asrofi Liza Nasution; Akim MH Pardede; Fuzy Yustika Manik (CV. AFDIFAL MAJU BERKAH, 2022)
The Trans Binjai Bus or Bus Rapid Transit (BRT) which is managed by the Binjai City Transportation Service is a bus system that is fast, comfortable, safe and on time. Each BRT system must use a different improvised system, although the improvements are shared with other BRT systems. The queue system in operations carried out by the Trans Binjai Bus often occurs overcrowding and even builds up at one point which results in Trans Binjai Bus users having to wait and not know the departure schedule. Therefore, the queuing system in the operation of the Trans Binjai bus must be carried out in a systematic and scheduled manner so that accumulation at one point and delays can be avoided. Queue is a waiting line situation where a number of physical units (entrants) are trying to receive service.